Wavelet Applications in Economics and Finance - Gallegati, Marco; Semmler, Willi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book deals with the application of wavelet and spectral methods for the analysis of nonlinear and dynamic processes in economics and finance. It reflects some of the latest developments in the area of wavelet methods applied to economics and finance. The topics include business cycle analysis, asset prices, financial econometrics, and forecasting. An introductory paper by James Ramsey, providing a personal retrospective of a decade's research on wavelet analysis, offers an excellent overview over the field.
Macroeconomics -- Volatility and Asset Prices -- Forecasting and Spectral Analysis.
Keywords: Economics; Economics -- Statistics; Econometrics; Economics/Management Science; Economic Theory; Statistics for Business/Economics/Mathematical Finance/Insurance.; Socio- and Econophysics, Population and Evolutionary Models; Finance/Investment/Banking.; Econometrics; Nonlinear Dynamics